ANALISIS KEPUASAN PELANGGAN PADA HOTEL RESTY MENARA PEKANBARU - Farhan, Rizky; Zuliarni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Customer satisfaction is a situation where the wishes,  expectations and customer requirements are met.  Customer satisfaction is defined as a form of consumer sentiment after comparing with their  expectations. Customer expectations on satisfaction, which is always  changing demands company professionality,  because satisfaction is indeed intercedes to improve quality ofservice.Based on the analysis to the Cartesian diagram Importance and Performance Analysis, there is one attribute that is entered into the first quadrant(Priority) which indicates the level of importance of these attributes considered important by consumers,  but the performance shown by this attribute is considered low or have not been maximal, that was  attribute 8 namelycompleteness and cleanliness of the rooms. There are three attributes that go intoquadrant II (Maintain Achievement) which shows attributes that are consideredimportant by consumers and the level of performance in line with expectationsconsumers. These Atribut were Attributes 2 (Health and Quality Menu), Attribute3 (Support Facility) and attribute 9 (Equipment Food) .there were three attributesinto the third quadrant (lower  priority)  which shows attributes that are considered less important by consumers and the level of performance in reality is not very good,  the attribute were attribute 1 (interior  room),  attribute 4(friendliness and sincerity), attribute 5 (fast response) and attribute 7 (standard room) . There was 1 attributes that go into quadrant IV (redundant) that showedlittle or no service attributes are important but the level of performance isconsidered excessive, the attributes was attribute 6 (Responsive and solution)Keyword : Cunsomers Satisfaction , Importance and Performance Analysis, IPA